Chemical Compositions of Two commonly consumed Insects in Kontagora Local Government Area, Niger State, Nigeria: Chemical Compositions of Two commonly consumed Insects in Kontagora Local Government Area, Niger State, Nigeria - Oriolowo, Olatayo; John, Joseph Othman; Olarongbe, Ganiyu Oladimeji (Sahel Journal of Life Sciences FUDMA, 2024)
The practice of entomophagy is culturally acceptable in many parts of Africa including Nigeria. Grasshopper Zonocerus varigatus and Dung beetle larva Aphodius rufipes are two major insects consumed by people of Kontagora local government area of Niger State, Nigeria. These insects are eaten for nutritional and health benefits and are highly priced as commercial commodities. Proximate, mineral elements and anti-nutrients and amino acids composition of these insects were determined using standard methods. The results showed crude protein content to be 41.6%, 42.3%; fat of 17.5%, 24.2%; ash of 7.2%, 4.3%; fibre of 14.1%, 4.6%; carbohydrate of 13.2%, 18.9% for grasshopper and dung beetle larva respectively. Nutrients like phosphorus, potassium, sodium, calcium and iron are of excellent quantity in both insects. About 44.4% and 66.7% respectively of essential amino acids in grasshopper and dung beetle larvae satisfy human nutritional requirements. The quantity of amino acids lysine, tryptophan and threonine are adequate in grasshopper and dung beetle larvae thereby making them complementary protein for limited cereals diets common to people in this region. Interestingly, a consumption of 97g and 46g of grasshopper and dung beetle larvae respectively could effectively satisfy the daily adult human amino acid requirement. Lastly, anti-nutrients like cyanide and oxalate present in these insects are of tolerable quantity for human consumption. Therefore both insects were recommended as alternatives to conventional sources of animal protein for the human diet.